Immunomodulatory Effect of MSC on B Cells Is Independent of Secreted Extracellular Vesicles - Carreras-Planella, Laura; Monguió-Tortajada, Marta; Borràs, Francesc Enric; Franquesa, Marcella (Frontiers in Immunology, 2019)
Mesenchymal stem cells (MSC) have proven immunomodulatory properties towards B cell activation and induce regulatory B cells (Breg), through a dual mechanism of action that relies both on cell contact and secreted factors. One of them are MSC-derived extracellular vesicles (EVs), membrane nanovesicles that mediate cell communication and typically reflect the phenotype of the cell of origin. MSC-EVs could resemble MSC functions, and are being contemplated as an improved alternative to the MSC-based immunomodulatory therapy. In the present work, we focused on the factors secreted by MSC and aimed to elucidate the putative role of MSC-EVs in the immunomodulation of B cells. EVs and soluble protein-enriched fractions (PF) were isolated from MSC-conditioned medium (CM) using size-exclusion chromatography (SEC) and their capacity to modulate B cell activation, induction of Breg and B cell proliferation was compared to that of the whole MSCs. Co-culture with MSC or unfractionated CM induced naïve and CD24hiCD38hi, IL-10 producing (Breg) phenotypes on B cells while not affecting proliferation. MSC-PF had a comparable effect to MSCs, inducing a naïve phenotype, and even though they did not induce the shift towards a CD24hiCD38hi population, MSC-PF fostered IL-10 production by B cells. Conversely, MSC-EVs failed to promote naïve B cells and to reduce memory B cells. MSC-EVs induced CD24hiCD38hi B cells to a similar extent of that of MSC, but not bona fide Bregs since they did not produce IL-10. Our results show that B cell modulation by MSC is partially mediated by soluble factors other than EVs.